The Effectiveness of WDEP Reality Counseling in Reducing Social Comparison Among Students - Jannah, Nuria Nurul; Rahmawati, Weni Kurnia; Fauziyah, Nailul; Mamahit, Henny Christine (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2025)
The excessive use of social media among adolescents has triggered the phenomenon of social comparison, which has a negative impact on mental health and academic performance. Existing interventions have not specifically addressed this issue, even though reality counseling has been proven effective for other psychological problems. This study aims to prove the effectiveness of WDEP reality counseling in reducing social comparison among students who use social media at SMK Muhammadiyah 1 Bondowoso. The method used is a Quasi-Experiment with a Pre-test Post-test Control Group Design, involving 10 students with moderate and high levels of social comparison. Five students were placed in the experimental group and five others in the control group. Data collection used the adapted INCOM scale, with validity (0.361-0.837) and reliability (0.895). In the basic assumption test, the pre-test and post-test results showed that all data were normally distributed and homogeneous, with a sig. value <0.05, allowing the use of the T-test to analyze score differences. The T-test results showed a significant decrease in social comparison scores in the experimental group from 92.00 to 67.40, compared to the control group, which only decreased from 89.20 to 87.60. These findings prove that WDEP reality counseling is effective and practical in helping students understand and manage their social behavior. This intervention is recommended for counselors and educational institutions as an intervention strategy to address students' psychological well-being issues.